Chinese university students’ conceptions of feedback and the relationships with self-regulated learning, self-efficacy, and English language achievement - Lu, Shasha; Cheng, Liying; Chahine, Saad (Frontiers in Psychology, 2022)
In China, under the influence of examination-driven culture and teacher-centered way of learning, students’ self-regulated learning (SRL) capabilities, self-efficacy, and the actual English proficiency are greatly hindered. Given this situation, the Chinese Ministry of Education has promulgated the use of formative assessment in the College English curriculum at the tertiary level since 2004. Feedback, as an integrated part of formative assessment, takes up the largest proportion of the Chinese College English classroom assessment and intends to facilitate SRL and learning. However, whether feedback could facilitate students’ SRL and learning has not been fully investigated in this context in China. Therefore, this study first explored how students self-reported their conceptions of feedback, SRL, self-efficacy and second, the relationships among these constructs and their English language achievement in the College English course. A questionnaire was used to collect data on students’ conceptions of feedback, SRL, self-efficacy and self-perceived English language proficiency. Their English test scores as an indicator of English language achievement were also collected. A total of 538 participants from a university in Northern China participated in this study. Data were analyzed using descriptive statistics, exploratory factor analyses, Pearson correlation analyses and multiple regression analyses. The results found that Chinese students from the College English course reported a high level of conceptions of teacher and peer feedback, SRL and self-efficacy, yet a low level of Teacher/Peer Feedback Ignored. For the relationships among these variables, students’ conceptions of feedback contributed to SRL and self-efficacy. Besides, self-efficacy was found to be the strongest predictor for self-perceived English language proficiency and standardized English test scores, both indicators for English language achievement. From the theoretical perspective, this study addressed the research gap in the literature by examining four constructs together, i.e., student conceptions of feedback, SRL, self-efficacy and English language achievement within a university context in China. From the pedagogical angle, the results can also support teachers on their feedback practices to facilitate students’ SRL, self-efficacy and learning.